Posterior Quadratus Lumborum Block versus Transversus Abdominis Plane Block with Bupivacaine and Dexmedetomidine for Postoperative Analgesia following Caesarean Delivery: A Randomised Clinical Study - V Rajesh Kumar Kodali; Kiran Muthu Rajah; Varun Karuppaiah Thiagarajan (Journal of Clinical and Diagnostic Research)
Introduction: Pain management after caesarean delivery is vital for the early recovery of the mother. In the absence of long-acting opioids, fascial plane blocks such as the Quadratus Lumborum Block (QLB) and Transversus Abdominis Plane (TAP) block significantly prolong the duration of analgesia and increase maternal comfort. Aim: To compare the number of rescue analgesic boluses required in the 24-hour postoperative period between the QLB and TAP block groups. Materials and Methods: This study was a prospective, single-blind, randomised clinical trail conducted in the Department of Anaesthesiology at a teritary care teaching Hospital, Chennai, Tamil Nadu from March 2021 to March 2022 on 94 patients (47 in each group) scheduled for elective Lower Segment Caesarean Section (LSCS) and were randomised into two groups: Group T and Group Q. Patients in Group T received a TAP block, while patients in Group Q received a QLB. The primary outcome assessed was the number of rescue analgesic boluses used in 24 hours. Secondary outcomes assessed included the time to initial onset of pain, time to the first request for analgesia, total amount of rescue analgesic consumption for 24 hours, and postoperative pain scores. The Chi-square test and Fisher-Freeman-Halton Exact test were utilised to compare the categorical variables. Results: Mean rescue bolus doses were significantly lower in Group Q (1.0±0.6 doses) compared to Group T (2.5±0.6 doses) (p<0.01). Total rescue analgesic consumption in Group Q (51 mg) was significantly lower than in Group T (127 mg) (p<0.01). The time to the initial onset of pain and time to the first rescue analgesia were significantly longer in Group Q (17.9 hours and 18.2 hours, respectively) than in Group T (11.9 hours and 12.2 hours, respectively) (p<0.01). Lower pain scores were noted from 12 hours to 24 hours in Group Q compared to Group T. Conclusion: The QLB with dexmedetomidine reduces the number of rescue boluses in 24 hours and decreases rescue analgesic consumption. The QLB also prolongs the initial onset of pain and the time to the first rescue analgesic, with lower pain scores from 12 to 24 hours compared to the TAP block group.